Reliability and Validity of a Flume-Based Maximal Oxygen Uptake Swimming Test - Elizabeth F. Nagle; Takashi Nagai; Anne Beethe; Mita Lovalekar; Meghan S. Tuite; Meaghan E. Beckner; Jacquelyn N. Zera; Mary E. Sanders; Chris Connaboy; John P. Abt; Kim Beals; Scott M. Lephart; et al. (MDPI AG, 2023)
A mode-specific swimming protocol to assess maximal aerobic uptake (VO2maxsw) is vital to accurately evaluate swimming performance. A need exists for reliable and valid swimming protocols that assess VO2maxsw in a flume environment. The purpose was to assess: (a) reliability and (b) "performance" validity of a VO2maxsw flume protocol using the 457-m freestyle pool performance swim (PS) test as the criterion. Nineteen males (n = 9) and females (n = 10) (age, 28.5 ± 8.3 years.; height, 174.7 ± 8.2 cm; mass, 72.9 ± 12.5 kg; %body fat, 21.4 ± 5.9) performed two flume VO2maxsw tests (VO2maxswA and VO2maxswB) and one PS test [457 m (469.4 ± 94.7 s)]. For test-retest reliability (Trials A vs. B), moderately strong relationships were established for VO2maxsw (mL·kg−1·min−1)(r= 0.628, p = 0.002), O2pulse (mL O2·beat−1)(r = 0.502, p = 0.014), VEmax (L·min−1) (r = 0.671, p = 0.001), final test time (sec) (0.608, p = 0.004), and immediate post-test blood lactate (IPE (BLa)) (0.716, p = 0.001). For performance validity, moderately strong relationships (p < 0.05) were found between VO2maxswA (r =−0.648, p = 0.005), O2pulse (r= −0.623, p = 0.008), VEmax (r = −0.509 p = 0.037), and 457-m swim times. The swimming flume protocol examined is a reliable and valid assessment of VO2maxsw., and offers an alternative for military, open water, or those seeking complementary forms of training to improve swimming performance.